L-theanine modulates tissue cortisol levels in zebrafish after single stress - Vinícius Luís da Silva; Mariana Spanamberg Mayer; Andriele dos Reis Severo; Andressa Leal Zambra; Joanna Moraes De Almeida; Laura Moura Sestari; Mariana Migliorini Parisi; Ana Cristina Vendrametto Varrone Giacomini; Murilo Sander De Abreu; Josiane Woutheres Bortolotto; Gabriela Bonfanti-Azzolin (Brazilian Journal of Pharmaceutical Sciences)
Abstract L-theanine has neuromodulatory properties, such as attenuate anxiety disorders and stress. Stress is a situation characterized by the stimulus to cortisol secretion and without specific pharmacological therapies. Thus, this study investigates the effect of L-theanine on the response to acute stress, evaluated by tissue cortisol level, oxidative status markers, and behavioral parameters, in zebrafish. The animals were divided into six groups: G1: control, G2: treated with L-theanine 45 mg/L, G3: treated with L-theanine 100 mg/L, G4: stress, G5: stress+L-theanine 45 mg/L and G6: stress+L-theanine 100 mg/L. Before the execution of the acute stress protocol that consisted of chasing the animals with a net for two minutes, exposure to L-theanine was performed in aquarium water for 1 hour. Tissue cortisol levels were analyzed, as well as cerebral oxidative status (lipoperoxidation and levels of thiolic compounds) and fish behavior (new tank test). L-theanine at a concentration of 45 mg/mL modulated the effects of acute stress on zebrafish, inhibiting increased levels of tissue cortisol. However, it was not able to alter the behavior or oxidative status of the animals. Thus, we conclude that the administration of L-theanine can promote acute stress attenuation, modulating the pathological responses of stress.